The effectiveness of Ya Dok Khao (Vernonia cinerea (L.) Less.) herbal products in reducing smoking behavior of people in Ban Kham Pa-O community, Kuddon sub-district, Huai Mek district, Kalasin Province - Srithanee, Kitpapon; Ruttanatam, Papavee; Loachai, Surattana; Puchomkaeo, Rani (SciTech Research Journal, 2022)
The purpose of this research was to study the smoking behavior of volunteers at Baan Kham Pa-O, Kuddon sub-district, Huai Mek district, Kalasin province. To compare the efficacy of Ya Dok Khao (Vernonia cinerea: VC) herbal candy products with herbal tea products, and to study the satisfaction of Ya Dok Khao (Vernonia cinerea: VC) herbal candy products with herbal tea products. The study samples were smokers aged 18-60 years in the area of ​​Ban Kham Pa-O, Kuddon subdistrict, Huai Mek district Kalasin province, 52 people were selected using a specific selection method based on the inclusion criteria. Data was collected by using a content validity of 0.92. The reliability was determined by using Cronbach's Alpha Coefficient of 0.867. The analysis of descriptive statistics were used such as frequency, percentage, mean and standard deviation and the inferential statistics was t-test. The results of the study found that the smoking behaviors of the volunteers were mostly daily smoking habits. The volume of smoke was between 10-20 cigarettes per day. Cigarettes smoked in packs or ready-made cigarettes. The time to smoke was the first cigarette after waking up was more than 60 minutes. The more likely to smoke was after eating and if they didn't smoke, they will have irritability. Vernonia cinerea herbal candy products with Vernonia cinerea herbal tea products has no difference in effectiveness in reducing the amount of smoking. The sample group was more satisfied with Vernonia cinerea herbal candy products than Vernonia cinerea herbal tea products at a statistically significant level of 0.05.